Characterising fatigue macrocrack initiation in profiled steel roof cladding. (15th October 2016) - Lovisa, A.C.; Henderson, D.J.; Ginger, J.D.; Walker, G.
Highlights: Corrugated roof cladding was subjected to constant amplitude loading. Crack growth was monitored to identify a critical crack length for crack initiation. The strain state in the vicinity of the fatigue crack was monitored during loading. At crack initiation, the principal strains followed a linear function. Abstract: In Australia and abroad screw-fixed, thin, high strength, profiled steel roof cladding systems are widely used on low rise industrial, commercial and residential buildings. Under extreme wind conditions, such as those produced by cyclones, these systems can fail as a result of low cycle metal fatigue. Current design of such systems is based entirely on standardised cyclic testing of full scale prototype assemblies. This paper describes the mechanism underlying this fatigue behaviour by studying the initiation of cracking in corrugated high strength steel cladding. When subject to repeated loading cracks initiate within the cladding at the fasteners, nucleating in the plane of maximum shear through the cladding thickness prior to propagating into the plane of the cladding. Crack initiation was considered to be the point in which the thickness of the cladding was entirely bisected and the crack was beginning to propagate into the plane of the cladding. Based on this characterisation, a crack initiation criterion dependent on the surface principal strains in the region of crack initiation was developed for both the longitudinal and transverse directions of the cladding. In combination with detailed stress analysis such criteria could be implemented in a numerical model to predict crack initiation in cladding, providing an analytical tool which could greatly assist the fatigue design process and lead to a reduction in the total reliance on prototype testing of each individual system used.